2008
DOI: 10.3379/msjmag.32.150
|View full text |Cite
|
Sign up to set email alerts
|

Magneto-optical Indicator Garnet Films Grown by Metal-organic Decomposition Method

Abstract: Bi-substituted yttrium iron garnet, Y3-xBixFe5O12 (Bi:YIG, x = 1, 1.5), films were prepared on Gd3Ga5O12 (111) substrates by metal-organic decomposition (MOD) method to use as MO indicator films. Those films had the in-plane magnetic anisotropy and Faraday rotation as large as that of the single crystal and do not show prominent magnetic domain structure, which is often observed in single crystalline garnet films grown by liquid phase epitaxy method. Disappearance o magnetic domain structure can be attributed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 12 publications
0
21
0
1
Order By: Relevance
“…We have reported that metal-organic decomposition ( MOD) method is promising to obtain high quality garnet films with high-bismuth content because they are advantageous not only for homogeneity of the thin film, the controllability of composition, and formation over large area but also for the good productivity and stability of the MOD solution for more than several years [11][12][13][14][15][16] . In previous work, we have also reported that Nd 2 BiFe 4 GaO 12 (Bi1:NIGG) layer is effective as a buffer layer to obtain Y 2 Bi 2.5 Fe 5 O 12 , x = 2.5, on glass substrates 15 .…”
Section: Introductionmentioning
confidence: 99%
“…We have reported that metal-organic decomposition ( MOD) method is promising to obtain high quality garnet films with high-bismuth content because they are advantageous not only for homogeneity of the thin film, the controllability of composition, and formation over large area but also for the good productivity and stability of the MOD solution for more than several years [11][12][13][14][15][16] . In previous work, we have also reported that Nd 2 BiFe 4 GaO 12 (Bi1:NIGG) layer is effective as a buffer layer to obtain Y 2 Bi 2.5 Fe 5 O 12 , x = 2.5, on glass substrates 15 .…”
Section: Introductionmentioning
confidence: 99%
“…Bi:YIG films grown by the MOD method allows us to measure clear MO images without zigzag-shaped magnetic domains as observed in LPE-grown garnet film [7]. Pt mirror layer with a thickness of 100 nm was deposited on the garnet film by a magnetron sputtering method in order to obtain high reflectivity and to avoid scattering of the light due to the pattern fabricated on the sample.…”
Section: Mo Imagingmentioning
confidence: 99%
“…In addition, quantitative MO imaging allows us to obtain current distributions in the superconductors. In order to realize quantitative MO imaging with highresolution and sensitivity, we have developed an MO microscope using polarization modulation technique [5] and MO indicator garnet films by metal-organic decomposition (MOD) method [6,7]. In this paper, we report on quantitative MO imaging of high quality MgB 2 thin films grown by a molecular beam epitaxy (MBE) method.…”
Section: Introductionmentioning
confidence: 98%
“…The MO imaging method has a much higher spatial and temporal resolution. Using the MO imaging method, not only the motion of the magnetic flux but also the distribution of the magnetic flux density in superconductors can be directly observed from the bright and dark patterns of the magnetic domain of a garnet film by using a polarizing light microscope [13]. From the asymmetry of the distribution, the intensity of the bulk pinning force along different directions of the applied current can be estimated.…”
Section: Introductionmentioning
confidence: 99%